Analysis of the Implementation of the Government's Internal Control System in Achieving Accountability in the One Stop Integrated Investment and Licensing Service of North Sumatra Province - M. Fadli Chaniago; Marliyah Marliyah (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze the Implementation of the Government's Internal Control System in Achieving Accountability in the Investment and One Stop Service Office of North Sumatra Province. Government Internal Control System (SPIP) is very important. This is an inherent responsibility of the Head of Regional Apparatus. The Government's Internal Control System is an integral process for actions and activities carried out continuously by the leadership and all employees to provide adequate confidence in the achievement of organizational goals through effective and efficient activities, reliability of financial reporting, safeguarding State assets, and compliance with regulations. legislation. This study uses descriptive qualitative research, this research was carried out at the Office of the One Stop Investment and Licensing Service Office of North Sumatra Province with data sources in the form of library research and field research consisting of observations, interviews and research. document. The data collected were analyzed using qualitative methods to describe and analyze a situation based on facts in order to obtain a complete picture of the implementation of the government's internal control system in realizing accountability in the One Stop Integrated Investment and Licensing Service of North Sumatra Province.